Digital terrain modeling and drainage modeling - Mohd Nasir Bin Nordin, Mohd Nasir (2009)
Digital Terrain Modeling (DTM) has always been the base for representing terrain. Combine with hydrologic modeling; this can help to provide the necessary information of the hydrologic cycle, inflow and outflow in the catchment area and the change in elevation of that particular area.